Micro-Shear Bond Strength of Infiltrated and Machined Lithium Disilicate Ceramics Treated with One-Step Self-Etching Adhesives - Dominguez, John Alexis (2020)
Objectives: evaluate the micro-shear bond strength in lithium disilicate ceramics with different manufacturing process treated with two one-step self-etching adhesives.